For genomes to stay in shape, insulators must be up to PAR. - Wijchers, P.J.; de Laat, W. (Cell, 2013)
Insulators drive nuclear organization by blocking or facilitating interactions between DNA regulatory elements. Ong et al. show that poly(ADP-ribosyl)ation of insulator binding proteins modulates their ability to physically interact with distant regulatory elements, implicating posttranslational modifications of nonhistone proteins in genome architecture.